2021
DOI: 10.2147/cia.s319891
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Severe Neurocognitive Impairment and Its Association with Socio-Demographics and Functionality Among Ugandan Older Persons: A Hospital-Based Study

Abstract: Background:The prevalence of neurocognitive disorders, especially dementia, is rising due to an increase in longevity. Early detection and diagnosis of neurocognitive impairments are important for early interventions and appropriate management of reversible causes, especially by the primary health workers. However, this study aimed to determine the prevalence and associated factors of severe neurocognitive impairment among elderly persons attending a tertiary hospital in Uganda. Methods: This cross-sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 56 publications
1
5
0
2
Order By: Relevance
“…This cross-sectional descriptive study was conducted in February 2021 among older adults aged 60 years and above attending a referral hospital outpatient clinic in Uganda that attends approximately 600 older adults every month [6,25]. After receiving care for various ailments, elders were recruited by convenience sampling after obtaining written consent from the outpatient departments.…”
Section: Study Design Setting and Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…This cross-sectional descriptive study was conducted in February 2021 among older adults aged 60 years and above attending a referral hospital outpatient clinic in Uganda that attends approximately 600 older adults every month [6,25]. After receiving care for various ailments, elders were recruited by convenience sampling after obtaining written consent from the outpatient departments.…”
Section: Study Design Setting and Populationmentioning
confidence: 99%
“…Financial abuse in this study was associated with increasing age above 80 years because individuals above 80 years are more vulnerable to abuse. After all, they are at higher risk of neurocognitive disorders and functional dependence, which makes them unable to manage their finances or forget to request financial assistance [6]. They may also be more likely to make poor financial decisions and fall victim to fraudulent deals [41].…”
Section: Financial Abusementioning
confidence: 99%
See 1 more Smart Citation
“…These observations are consistent with previous reports from Uganda and beyond. [ 20 , 21 , 30 , 31 ] In this study, all cases of seizures were reported in patients with cognitive deficits.…”
Section: Discussionmentioning
confidence: 96%
“…Among older persons in western Uganda, severe cognitive impairment was observed in 28% of the participants. [ 30 ] Another study from rural Uganda reported a dementia prevalence of 20% among the general population of persons older than 60 years. [ 31 ] On the other hand, Mukisa and colleagues reported a 20% prevalence of dementia among patients who recently recovered from stroke.…”
Section: Discussionmentioning
confidence: 99%